Expert validation of the COVID-2019 Peri-traumatic Distress Index for use in Peru. - Pedraz-Petrozzi, Bruno (2021)
Objectives: To perform an expert validation study of COVID-19 Peritraumatic Distress Index (CPDI) for its eventual use in Perú. Material and Methods: In a first round by experts, the CPDI was translated into Spanish and then adapted. In a second round, (n = 13), the content validity was evaluated by using Aiken’s V (V). The V was calculated for each item, as well as for the whole instrument (VTOT). Results: Of the 24 original items, only one (S7) presented non-significant values for content validity, reason for which it was removed. The final 23-items scale did not present any alterations for the VTOT calculation Conclusions: On the basis of its adequate content validity, the Spanish version of CPDI is suitable for its application in the Peruvian population. The psychometric characteristics of the instrument, as well as its proposed modification remain to be defined through quantitative studies of the construct validity.